Evaluation of six commercial products for colistin susceptibility testing in Enterobacterales. (November 2019) - Pfennigwerth, N.; Kaminski, A.; Korte-Berwanger, M.; Pfeifer, Y.; Simon, M.; Werner, G.; Jantsch, J.; Marlinghaus, L.; Gatermann, S.G.
Abstract: Objectives: The recommended technique for colistin susceptibility testing by both EUCAST and CLSI is broth microdilution (BMD). However, many routine laboratories still use other methods such as gradient strips or semi-automated systems. The objective of this study was to compare six of the most widespread commercial products for colistin susceptibility testing in Europe with in-house prepared BMD. Methods: A collection of 325 carbapenemase-producing Enterobacterales was tested for colistin susceptibility with three semi-automated systems (Vitek 2, BD Phoenix, MicroScan WalkAway), one gradient-strip test (Etest®) and two commercial BMD products (MICRONAUT-S, TREK Sensititre). BMD, in-house prepared according to ISO standard 20776-1, served as reference. Results: The MICRONAUT-S BMD performed best with only one false-resistant (major error, ME) and four false-susceptible (very major error, VME) results while the TREK BMD performed poorer with 16 ME and seven VME. The semi-automated systems Vitek 2 and Phoenix performed poorly with 31 and 26 VME, respectively. The WalkAway semi-automated system showed 16 and 13 false results, depending on the inoculation method. The Etest® showed six ME and 10 VME. Conclusions: This study shows that colistin susceptibility testing remains a challenging task for laboratories. It emphasizes the need for selecting the most reliable test method to advocate proper treatment and shows that critical evaluation and precautious usage of colistin susceptibility testing results is constantly required.